THE ATACAMA COSMOLOGY TELESCOPE: DYNAMICAL MASSES AND SCALING RELATIONS FOR A SAMPLE OF MASSIVE SUNYAEV-ZEL'DOVICH EFFECT SELECTED GALAXY CLUSTERS - Sifon, C; Menanteau, F; Hasselfield, M; Marriage, T; Hughes, J; Felipe Barrientos, L; Gonzalez, J; Infante, L; Addison, G; Baker, A; Battaglia, N; Bond, JR; et al. (Institute of Physics Publishing, 2013)
We present the first dynamical mass estimates and scaling relations for a sample of Sunyaev-Zel'dovich effect (SZE) selected galaxy clusters. The sample consists of 16 massive clusters detected with the Atacama Cosmology Telescope (ACT) over a 455 deg2 area of the southern sky. Deep multi-object spectroscopic observations were taken to secure intermediate-resolution (R ∼ 700-800) spectra and redshifts for 60 member galaxies on average per cluster. The dynamical masses M 200c of the clusters have been calculated using simulation-based scaling relations between velocity dispersion and mass. The sample has a median redshift z = 0.50 and a median mass with a lower limit , consistent with the expectations for the ACT southern sky survey. These masses are compared to the ACT SZE properties of the sample, specifically, the match-filtered central SZE amplitude , the central Compton parameter y 0, and the integrated Compton signal Y 200c , which we use to derive SZE-mass scaling relations. All SZE estimators correlate with dynamical mass with low intrinsic scatter (≲ 20%), in agreement with numerical simulations. We explore the effects of various systematic effects on these scaling relations, including the correlation between observables and the influence of dynamically disturbed clusters. Using the three-dimensional information available, we divide the sample into relaxed and disturbed clusters and find that ∼50% of the clusters are disturbed. There are hints that disturbed systems might bias the scaling relations, but given the current sample sizes, these differences are not significant; further studies including more clusters are required to assess the impact of these clusters on the scaling relations. © 2013. The American Astronomical Society. All rights reserved.